2011
DOI: 10.1080/13825585.2011.586018
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive aging and flight performances in general aviation pilots

Abstract: Unlike professional pilots who are limited by the FAA's age rule, no age limit is defined in general aviation. Our overall goal was to examine how age-related cognitive decline impacts piloting performance and weather-related decision-making. This study relied on three components: cognitive assessment (in particular executive functioning), pilot characteristics (age and flight experience), and flight performance. The results suggest that in comparison to chronological age, cognitive assessment is a better crit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
1

Relationship

2
7

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 52 publications
0
20
1
Order By: Relevance
“…First, the DLPFC is a brain structure involved in working memory (WM), an executive function dedicated to storing and updating information (see Curtis & Esposito, 2004). Accordingly, a temporary lack of WM capacity is likely to induce perseveration since the inability to upgrade situation awareness, in line with unexpected events, can lead to the continuation of schemes of action that are no longer appropriate in the current circumstances (Causse, Dehais, Arexis, & Pastor, 2011;Orasanu, Martin, & Davison, 2001). Second, it has been PERSEVERATION IN HUMAN ERROR proposed that the DLPFC is the neural substrate of the supervisory attentional system that arbitrates conflicts between competitive responses to stimuli (Norman & Shallice, 1986).…”
Section: Perseveration In Human Errormentioning
confidence: 99%
See 1 more Smart Citation
“…First, the DLPFC is a brain structure involved in working memory (WM), an executive function dedicated to storing and updating information (see Curtis & Esposito, 2004). Accordingly, a temporary lack of WM capacity is likely to induce perseveration since the inability to upgrade situation awareness, in line with unexpected events, can lead to the continuation of schemes of action that are no longer appropriate in the current circumstances (Causse, Dehais, Arexis, & Pastor, 2011;Orasanu, Martin, & Davison, 2001). Second, it has been PERSEVERATION IN HUMAN ERROR proposed that the DLPFC is the neural substrate of the supervisory attentional system that arbitrates conflicts between competitive responses to stimuli (Norman & Shallice, 1986).…”
Section: Perseveration In Human Errormentioning
confidence: 99%
“…This ability to adapt strategy in line with changing circumstances is important in everyday situations, and particularly for the operators of dynamic and complex critical systems. For example, piloting an airplane involves adaptation to continually evolving scenarios, and mental flexibility as measured by one of the performance metrics on the WCST has proven successful in predicting pilot perseveration in a subsequent flight simulation (Causse, Dehais, Arexis, & Pastor, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, as described earlier, those who did not choose to continue under sub-optimal conditions (i.e., chose to go-around), employed more efficient scanning strategies (e.g., higher number of and shorter fixations on information that permitted insight in to upcoming events; see Reynal et al, 2017) . Good decision makers had higher working memory capacity and greater attentional flexibility (Causse et al, 2011a), were better at risk assessment (Hunter et al, 2011), and exhibited lower impulsivity (Causse et al, 2011b, Behrend, Dehais, Koechlin, 2017. Subsequent research has also shown that when monetary incentive and uncertainty were manipulated in the helicopter landing decision task, risky decision makers exhibited lower activation of the prefrontal areas (i.e., dorso-lateral prefrontal cortex and anterior cingulate cortex) than good decision makers.…”
Section: Decision and Judgmentmentioning
confidence: 99%
“…However, a famous study conducted at MIT (Rhoda & Pawlak, 1999) demonstrated that, in 2000 cases of approaches performed under thunderstorm conditions, two aircrews out of three continued the flight plan and erroneously persisted with approach and landing. While several cognitive theories have been proposed to explain this result (Causse, Dehais, Arexis, & Pastor, 2011;Goh & Wiegmann, 2002), it may be that PCE is favored by strong negative emotions associated with the decision to revise the flight plan. These negative emotional consequences could adversely alter a pilot's rational reasoning by biasing decision-making criteria, thereby unconsciously affecting their risk assessments and the subsequent course of action chosen.…”
Section: Introductionmentioning
confidence: 99%